Evaluating Groundwater Quality in the Asante Akyem Central District of Ghana - Augustine Owusu Sekyere; Helen Essandoh; David Dotse Wemegah; Lydia Otoo Amponsah (SAGE Publishing, 2023)
Groundwater is the primary water supply source for many people living on the surface of the earth. They depend on this valuable resource for their daily needs. But this natural resource is continuously being threatened by both natural and anthropogenic activities. Therefore, continuous monitoring and assessment of the water quality of this resource is important to keep check of the effects of water contaminants especially on human health. This study assessed the levels of Fe, Cd, Mn, and Hg in hand-dug wells at 4 communities (Ahyiayem, Odumasi Zongo, Apeboaso, and Kwaakyewaso) in the Asante Akyem Central District of Ghana and evaluated its sources and potential health risk associated with their exposure. These communities are known for illegal small-scale mining. The analysis also included other water quality parameters such as pH, nitrate, potassium, sodium, total hardness, calcium hardness, Phosphate, chloride, and total dissolved solids. From the research, there was no carcinogenic health risk to the communities concerning Fe, Mn, and Hg through ingestion and dermal contact because the hazard quotients and health hazard indices recorded in both adults and children were below one (<1). However, from the research, Cd exhibited carcinogenic health risk because its Cancer risk (CR) index exceeded 10 -6 for both adults and children. This implies that there is a risk of cancer infection from ingesting water from the hand-dug wells in the study areas. According to the analysis of the Water Quality Index (WQI), the wells at Ahyiayem, Apeboaso, and Kwaakyewaso recorded indexes that were between 15 and 50, signifying that the hand-dug wells in these communities are safe for human consumption. However, about 90% of the wells at Odumasi Zongo recorded WQI values that were between 80 and 320. This means the hand-dug wells at Odumasi Zongo are highly polluted and not safe for human consumption.